2018
DOI: 10.2495/sdp-v13-n7-985-996
|View full text |Cite
|
Sign up to set email alerts
|

High density architecture as local factory of circular economy

Abstract: For at least two decades, Chile has witnessed intensive processes of urban regeneration, mainly by a densification of vast areas. This article offers a new review of residential densification, not through the lens of building height or architectural massiveness, but rather by considering residential density as an opportunity to introduce circular economy cycles on a local scale. The article supports the hypothesis that a building, with a high concentration of households, is a chance to induce a smallscale alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…A further important finding of the current study is that of the negative association between economic capital and residential expansion, and the relationship is just the reverse between economic capital and residential densification. This is supported by the study of Valenzuela et al [134], which is an innovative study of residential densification that views residential density as an opportunity to implement circular economy cycles at the local level. Economic output is found to be higher in high-density built areas as shown by Li [135] who indicated that the urban structures that have evolved from low polycentricity and low dispersion to high polycentricity and low dispersion have undergone the highest per capita GDP growth.…”
Section: Discussionmentioning
confidence: 88%
“…A further important finding of the current study is that of the negative association between economic capital and residential expansion, and the relationship is just the reverse between economic capital and residential densification. This is supported by the study of Valenzuela et al [134], which is an innovative study of residential densification that views residential density as an opportunity to implement circular economy cycles at the local level. Economic output is found to be higher in high-density built areas as shown by Li [135] who indicated that the urban structures that have evolved from low polycentricity and low dispersion to high polycentricity and low dispersion have undergone the highest per capita GDP growth.…”
Section: Discussionmentioning
confidence: 88%
“…Buildings also can use an economic model that reduces consumption, the collapse of the ecosystem, and the waste of finite resources by continually reusing materials and energy. The product and services can be redefined in architectural design using the concept of circular economy (Valenzuela et al, 2018). Architectural enterprises have shifted from the traditional linear model to the circular economy by considering the end-life perspective (Laumann & Tambo, 2018).…”
Section: Economymentioning
confidence: 99%